The influence of the cultural entrepreneur on the performance of cultural and creative firms. Issue 2 (10th August 2018) - Orihuela-Gallardo, Francisca; Fernández-Alles, Mariluz; Ruiz-Navarro, José
Abstract : Purpose: The purpose of this paper is to analyse the influence of the profile of cultural entrepreneurs (CE), in terms of their demographic characteristics and resources, on the performance of cultural and creative firms (CCFs). Design/methodology/approach: Departing from demographic theory and resource-based view, two hypotheses have been formulated and empirically tested, using a multiple regression model, with a sample of 80 Spanish CCFs. The CCF performance has been measured through two objective (employment growth and profitability) and one subjective/perceptual measurements (satisfaction of the CE with the attainment of objectives). Findings: With respect to the demographic variables, a negative relationship between the CE's age and employment growth, and a partial positive influence of the CE's prior experience on employment growth and the subjective measurement of performance have been found. Regarding to the CE's resources, the empirical evidence shows that there is no direct relationship between the CE's possession of any resources studied − financial, knowledge and social connections − and CCF performance. Originality/value: This work makes three important contributions as it analyses the CE and focuses on CCF management, a topic little discussed in the entrepreneurship literature. Second, there is an analysis of some of the variables pertaining to the entrepreneur's demographic profile that have been applied to top management teams and in a more or less isolated way in the entrepreneurship area. And, finally, a multidimensional measurement is used to explain the CCF performance. Abstract : Propósito: El propósito de este artículo es analizar la influencia del perfil de los emprendedores culturales (EC), en relación a sus características demográficas y los recursos que posee, sobre el rendimiento de las empresas culturales y creativas (ECCs) creadas y dirigidas por ellos. Diseño/metodología/enfoque: A partir de la Teoría Demográfica y la Teoría Basada en los Recursos, se han formulado dos hipótesis que han sido testadas empíricamente, usando un modelo de regresión múltiple, sobre una muestra de 80 ECCs españolas. Para medir el rendimiento de la ECC, se han utilizado dos medidas objetivas (crecimiento del empleo y rentabilidad) y una subjetiva (grado de satisfacción del EC con la consecución de los objetivos). Resultados: El estudio realizado pone de manifiesto, respecto a las variables demográficas, una relación negativa entre la edad del EC y el crecimiento del empleo, y una influencia positiva parcial de la experiencia previa del EC sobre el crecimiento del empleo y la medida subjetiva del rendimiento. En cuanto a los recursos del EC, nuestros resultados muestran que no existe relación directa entre la posesión de los recursos analizados —financieros, de conocimiento y sociales— y el rendimiento de la ECC. Originalidad/valor: Este trabajo realiza tres contribuciones importantes, ya que analiza la figura del CE, centrándose en la dirección de las ECCs, un tema poco estudiado en la literatura de emprendimiento. Se estudian algunas variables del perfil demográfico del emprendedor que han sido aplicadas a equipos de alta dirección y de manera más o menos aislada en el campo del emprendimiento. Y, finalmente, se utiliza una medida multidimensional para explicar el rendimiento de las ECCs.